World history of design - Margolin, Victor 1941- (London Bloomsbury Academic, 2015)
"Authored by pre-eminent design scholar Victor Margolin, World History of Design is an indispensable new multi-volume work, providing a comprehensive and detailed historical account of design from prehistory to the end of the twentieth century" -- Provided by publisher.
Machine generated contents note: -- Volume 1 -- Prehistoric Times to World War I -- 1. Tool making and Rock Art in the Prehistoric Age -- 2. The Earliest Civilizations and Their Inventions, 7000 BCE - 900 BCE -- 3. The Classical Age, 900 BCE - 800 CE -- 4. The Emergence of Societies, Dynasties, and Empires, 800 CE - 1200 CE -- 5. Europe from the Renaissance to the Industrial Revolution, 1200 CE - 1750 CE -- 6. The World outside Europe, 1200 - 1750 -- 7. The Industrial Revolution in Europe and America, 1750 CE -1830 CE -- 8. The Age of Exhibitions: Great Britain, 1830 CE - 1900 CE -- 9. The Craft Ideal and the Art Movement in Britain, 1861 - 1915 -- 10. Canada, Australia, New Zealand, 1300 CE - 1900 CE -- 11. The Age of Exhibitions: Europe Outside Great Britain,1830 CE - 1900 C.E. -- 12. Colonies and Pre-industrial Nations in Asia and Africa, 1750 CE - 1900 CE -- 13. Protoindustrialization in Diverse Regions, 1750 CE - 1900 CE -- 14. The United States: Mechanization Takes Command, 1840-1900 -- 15. Art Nouveau and the Decorative Impulse, 1890 - 1914 -- 16. The Beginnings of Modern Design in Europe and America, 1900-1917 -- 17. World War I, 1914-1918Volume 2 -- World War I to World War II -- 18. The Avant-Gardes, 1906 - 1925 -- 19. Design in the Soviet Union, 1917-1928 -- 20. Weimar Germany, 1918-1933 -- 21. France between the Wars, 1918 - 1939 -- 22. Tradition and Modernism: The English Compromise, 1918-1939: -- 23. Canada, Australia, New Zealand -- 24. The Low Countries, Austria, Switzerland, and Spain, 1918-1939 -- 25. Tradition and Modernism in Scandinavia,1918-1939 -- 26. The United States, 1918-1941 -- 27. Central and Eastern Europe, 1918-1939 -- 28. Design under the Dictators: Italy, Germany, Portugal, Soviet Union, 1922-1940 -- 29. Japan's Hybrid Modernity, 1900 - 1937 -- 30. India, China, and Southeast Asia, 1900-1937 23,284 -- 31. Latin America, 1900-1939 -- 32. Near and Middle East, 1900-1939 -- 33. Africa, 1900-1939 -- 34. World War II.
Includes bibliographical references and index.
Keywords: Design -- History